Analytical Study Of Goalkeeper Positioning Using MH System For Free Kick In Soccer - Zaidam, Mahdi; Hamid, Huda (Journal of Physical Education, 2019)
All sports have witnessed great development recently due to the scientific development in athletic achievements. Soccer is considered one of the most important team sport in which players should be fully aware of these developments especially in training, technology and mechanics. The goalkeeper is the key element in a team thus the aim of the study was to find a suitable mean for developing goalkeepers through using electronic system that specify his position during direct free kicks due to its great importance in achieving goals.